2002
DOI: 10.1590/s0103-90162002000300013
|View full text |Cite
|
Sign up to set email alerts
|

Water salinity and initial development of yellow passion fruit

Abstract: Considering the lack of information on salt tolerance of passion fruit (Passiflora edulis) seedlings, a study was carried out to evaluate the effects of water salinity on the vigor and initial growth in a completely randomized design with 8 levels of electrical conductivity of irrigation water (EC w ), varying from 1.0 to 8.0 dS m -1 . Salinity delayed the germination process, but relative reduction was observed only above EC w 4.43 dS m -1 . Seedling vigor and growth decreased with increasing salinity, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
1
7
0
10
Order By: Relevance
“…The process of plant establishment, which includes germination, growth and survival, is very susceptible to damage caused by salinity and such effects tend to intensify with the age of the plants (Soares et al, 2002) as observed in P. mucronata and C. rosea in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…The process of plant establishment, which includes germination, growth and survival, is very susceptible to damage caused by salinity and such effects tend to intensify with the age of the plants (Soares et al, 2002) as observed in P. mucronata and C. rosea in the present study.…”
Section: Discussionsupporting
confidence: 63%
“…O efeito dos sais sobre a germinação e o estabelecimento das plântulas pode correlacionar-se tanto aos efeitos de natureza física, uma vez que a salinidade diminui o potencial osmótico da solução do solo, o que faz com que a absorção de água pelas sementes e raízes seja mais difícil, e devido a efeitos tóxicos passíveis de ocorrer por ação direta de íons específicos ou por desordem nutricional (Soares et al, 2002 . Acima desses níveis de salinidade houve redução significativa do comprimento da PA das plântulas demonstrando o efeito dos sais sobre o seu crescimento.…”
Section: Resultsunclassified
“…Soares et al (2002) verificaram, para o nível de salinidade de 8 dS m -1 , que houve reduções na massa seca da PA e das raízes, respectivamente, de 27,3% e 37% em maracujazeiro-amarelo durante a fase de emergência das plântulas.…”
Section: Bunclassified
“…Em concentrações de cama de aviário acima desses níveis, provavelmente o crescimento das raízes seja limitado tanto pela salinidade elevada quanto pela volatilização de amônia (SOARES et al, 2002;CRUZ et al, 2006;QI et al, 2012), com impactos no crescimento da parte aérea pela absorção limitada de nutrientes e água. A redução do crescimento por concentrações acima de 24,17% discorda dos resultados publicados por DAVID et al (2008), que observaram maior comprimento das raízes e maior número de folhas de mudas de maracujazeiro quando adicionaram até 40% de cama de frango em terra de barranco.…”
Section: Estimates and Its Confidence Intervals For The Parameters Ofunclassified
“…Há relatos na literatura de maior crescimento de mudas de maracujazeiro-amarelo com até 40 % de cama de frango em mistura com solo (DAVID et al, 2008). Porém, seu uso em concentrações maiores como substituto de substratos orgânicos (puros ou em mistura) poderia reduzir o desenvolvimento do maracujazeiro devido à salinidade elevada (SOARES et al, 2002;CRUZ et al, 2006) e devido à decomposição, com formação de amônia e CO 2 , alterações no pH e na temperatura (TUOMELA et al, 2000). O composto de dejetos de suínos, por ser um material já estabilizado (OLIVEIRA & HIGARASHI, 2006), poderia ser usado em maior concentração na composição de substratos.…”
Section: Introductionunclassified